2015
DOI: 10.1177/0025802415605536
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of patients’ awareness of their rights in teaching hospitals in Iran

Abstract: Health-care professionals can provide care based on patients' rights, and their knowledge of patients' rights needs to be evaluated. Educational programmes, leaflets, booklets and posters can be helpful in this regard. In addition, professional organisations and the Ministry of Health need to be more sensitive to this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 10 publications
(16 reference statements)
0
13
0
Order By: Relevance
“…According to Bazmi et al [24], patients assigned the highest score to confidentiality of information with the doctors and the medical team. This can be due to the instruments used or the year of the study, because in Bazmi’s study, patient’s rights charter had 5 dimensions, but presently, there are13 dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…According to Bazmi et al [24], patients assigned the highest score to confidentiality of information with the doctors and the medical team. This can be due to the instruments used or the year of the study, because in Bazmi’s study, patient’s rights charter had 5 dimensions, but presently, there are13 dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…Although apparently an important subject to Iranian medical professionals, only a limited number of noncomprehensive studies have been conducted on medical professionalism in Iran. [14] Evidence suggests that the subject of professionalism is not taught or assessed as part of medical students’ curricula, especially in the case of general medicine and residency programs. Assessing the knowledge of medical professionalism in medical students and physicians helps identify the weaknesses of professionalism training and devise plans for future training on the subject.…”
Section: Introductionmentioning
confidence: 99%
“…However, research performed by Bazmi et al in 2015 on the patients' awareness of their rights reported that the level of awareness was 80%. 11 The results of the current study demonstrated that education level has a significant impact on the level of awareness of patient's rights. Most of the contributors who held university degrees believed that they have the right to access their medical records; meanwhile, most of the patients with low education levels believed they had no such right.…”
Section: Discussionmentioning
confidence: 56%